2019
DOI: 10.3389/fendo.2019.00518
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel MicroRNAs and Characterization of MicroRNA Expression Profiles in Zebrafish Ovarian Follicular Cells

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs that regulate gene expression primarily at the post-transcriptional levels and thereby play important roles in regulating many physiological and developmental processes. Oocyte maturation in fish is induced by hormones produced from the hypothalamus, pituitary, and ovary. Gonadotropin-releasing hormone (GnRH) stimulates the secretion of luteinizing hormone (LH), which in turn, induces the secretion of maturation-inducing hormone (MIH) from the ovary. It is documente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 84 publications
(94 reference statements)
0
13
0
Order By: Relevance
“…The ErB signaling pathway [65] and the cAMP signaling pathway [66] positively regulates GnRH secretion. Ssc-miR-181a is the hub miRNA in the sub-CeNET, and it is reported that miR-181a was participated the ovarian follicle development [67]. Here ssc-miR-181a was predicted to target PAK6.…”
Section: Discussionmentioning
confidence: 96%
“…The ErB signaling pathway [65] and the cAMP signaling pathway [66] positively regulates GnRH secretion. Ssc-miR-181a is the hub miRNA in the sub-CeNET, and it is reported that miR-181a was participated the ovarian follicle development [67]. Here ssc-miR-181a was predicted to target PAK6.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, in zebra fish it is believed that small early vitellogenic follicles are unable to undergo oocyte maturation whereas oocytes in mid-to late vitellogenic follicles can be induced by Luteinizing hormone (LH) to become matured. With this respect, several miRNAs were found to be abundantly expressed in the follicular cells from early vitellogenic and mid-to late vitellogenic stages follicles but the expression patterns of 24 miRNAs including miR-22a-3p, miR-16a, miR-181a-3p, and miR-29a were altered in follicles that were unable to undergo oocyte maturation [34].…”
Section: The Role Of Cellular Mirnas In Follicular Development and Oomentioning
confidence: 97%
“…When treated with human chorionic gonadotropin (hCG) and forskolin, it significantly repressed the expression of miR-17a and miR-430b in cultured follicular cells, thus depicting a clear role of these miRNAs in facilitating hormonal regulation of gene expression. A recent expression profiling study also identified 24 differentially regulated miRNA transcripts in Type IIIa and IIIb zebrafish follicles that included miR-16a, miR-22a-3p, miR-29a and miR-181a-3p (Zayed et al 2019). This study also found miR-202-5p to be the most abundant transcript in the vitellogenin follicles and suggested its involvement in follicle development and oocyte maturation.…”
Section: Zebrafish (Danio Rerio)mentioning
confidence: 62%
“…A recent expression profiling study also identified 24 differentially regulated miRNA transcripts in Type IIIa and IIIb zebrafish follicles that included miR‐16a, miR‐22a‐3p, miR‐29a and miR‐181a‐3p (Zayed et al . 2019). This study also found miR‐202‐5p to be the most abundant transcript in the vitellogenin follicles and suggested its involvement in follicle development and oocyte maturation.…”
Section: Zebrafish (Danio Rerio)mentioning
confidence: 99%